Strategi Pengembangan Wisata Puncak Jowin Untuk Meningkatkan Jumlah Kunjungan Wisatawan Di Kabupaten Tulungagung - Antamayuan S, Moch Verry Martin; Preswari, Yasmin Indra; Putri, Winda Istiqlaliya (FEB Universitas Maritim Semarang, 2024)
Thesis with the title Jowin Peak Tourism Development Strategy to Increase the Number of Tourist Visits in Tulungagung Regency